Hypertriglyceridemia - Induced Acute Pancreatitis in Pregnancy - Aziz Pridianto, Faris; Sunarko, Agung (Indonesian Journal of Obstetrics and Gynecology, 2024)
Introduction: Acute pancreatitis in pregnancy (APIP) is a rare case. The mortality rate for pregnant women due to pancreatitis is reported at 37 percent and fetal mortality rate is up to 60percent. Hypertriglyceridemia (4percent-10percent) is known as the third most common cause of acute pancreatitis. There is one study reported that hypertriglyceridemia-induced acute pancreatitis (HTGP) reached up to 56percent of APIP cases. CasePresentation: A 33-year-old woman, GIIIP2002 32/33 weeks came with shortness of breath, preceded by severe heartburn, nausea and fever. There was a decrease in consciousness, with high blood pressure, and tachycardia. The patient had no history of high blood pressure during routine ANC. From the laboratory results, leukocytes were 22,670/pL, random blood sugar level 713 mg/dL, severe metabolic acidosis on the results of blood gas analysis, amylase was 1,004.8 U/L, lipase was 899.4 U/L, and triglyceride was 789 mg/dL. From the results of an abdominal CT scan with contrast, were consistent with the description of acute pancreatitis. Discussion: In pregnant patients with severe heartburn, with no previous history of high blood pressure, it may be suspected to be caused by an acute pancreatitis. If there are no risk factors of alcohol abuse, hypertiglyceridemia can be suspected as the cause. Triglycerides normally increase during pregnancy, but their values do not reach a concentration that can cause an acute pancreatitis. Conclusion: Patients with risk factors for increased triglycerides, both in patients and families, require strict monitoring. Quick diagnosis and appropriate therapy are the keys to treat acute pancreatitis. Keywords: Acute pancreatitis, hypertriglyceridemia, pregnancy, preeclampsia